Community-Driven Brakes on Violent Extremism: The Case of Non-Radicalization of the Czech Romani Minority - Kocmanová, Markéta (Crime & delinquency, 2025)
This paper introduces intra-community brakes on domestic violent extremism within the Czech Romani minority. We discuss how the community’s ties to nonviolent networks, approach to ideology, and family attachment worked against manifestations of violent extremism during three major episodes of political violence affecting the Romani in Czechia. The study draws on extensive empirical data gathered through ethnographic and netnographic methods and analytical tools provided by constructivist grounded theory for data analysis. Our work aims to contribute to the growing body of scholarship on the role of protective factors in preventing engagement in extreme forms of political violence. It would also like to encourage scholarly debate on the notion of marginalized groups as active agents maintaining security within their own communities.